Pengaruh Budaya Organisasi Dan Komitmen Terhadap Kinerja Karyawan Pada Koperasi Syariah Rabani Kota Serang - Putri Apriyanti; Muhammad Gandung (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this research is to analyze the effect of Organizational Culture and Commitment on Employee Performance at Koperasi Syariah Rabani, Serang City. This study employs a quantitative method with an associative approach. Data were collected from 66 respondents through a questionnaire consisting of indicators of Organizational Culture (X₁), Commitment (X₂), and Employee Performance (Y). The data analysis includes validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The results show that Organizational Culture has a significant effect on Employee Performance, with a coefficient of determination of 17.5% and tcount > ttable (3.685 > 1.998). Commitment also has a significant effect on Employee Performance, with a coefficient of determination of 65.6% and tcount > ttable (11.040 > 1.998). Simultaneously, Organizational Culture and Commitment significantly influence Employee Performance, as indicated by the regression equation Y = 2.958 + 0.198X₁ + 0.626X₂, with a coefficient of determination (R²) of 70.6%, while the remaining 29.4% is influenced by other factors not examined in this study. The F-test result (79.124 > 3.14) confirms the simultaneous significance of both independent variables. Therefore, it can be concluded that Organizational Culture (X₁) and Commitment (X₂) have a positive and significant simultaneous effect on Employee Performance (Y) at Koperasi Syariah Rabani, Serang City.